2021
DOI: 10.1038/s41538-021-00114-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico characterization of adiponectin-receptor agonist dipeptides

Abstract: The aim of this study is to develop a dipeptide showing an adiponectin receptor 1 (AdipoR1) agonistic effect in skeletal muscle L6 myotubes. Based on the structure of the AdipoR1 agonist, AdipoRon, 15 synthetic dipeptides were targeted to promote glucose uptake in L6 myotubes. Tyr-Pro showed a significant increase in glucose uptake among the dipeptides, while other dipeptides, including Pro-Tyr, failed to exert this effect. Tyr-Pro induces glucose transporter 4 (Glut4) expression in the plasma membrane, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…This simulation revealed that elevated adiponectin-like AMPK/Glut4 translocation was induced in L6 myotubes. 14 The MD simulation analysis also indicated that YP was stably located, with a high binding affinity of ΔG bind < −10 kcal/mol, at the inner side of the two binding pockets (sites 1/2) of the seven-transmembrane receptor, AdipoR1, that was anchored in a virtual 1palmitoyl-2-oleoyl-phosphatidylcholine (POPC) membrane.…”
Section: ■ Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This simulation revealed that elevated adiponectin-like AMPK/Glut4 translocation was induced in L6 myotubes. 14 The MD simulation analysis also indicated that YP was stably located, with a high binding affinity of ΔG bind < −10 kcal/mol, at the inner side of the two binding pockets (sites 1/2) of the seven-transmembrane receptor, AdipoR1, that was anchored in a virtual 1palmitoyl-2-oleoyl-phosphatidylcholine (POPC) membrane.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Soybean proteins were studied because the intake of soybean proteins is reportedly effective in preventing NIDDM, 15 and they possess 17 YP-related tripeptide sequences ( tripeptide candidates were found in the soybean protein sequence, we determined the molecular interaction between the ligand tripeptide and AdipoR1 protein using CHARMM-GUI-aided MD simulation analysis. 14,16 ■ MATERIALS AND METHODS Chemicals. AdipoRon (>98% pure) was purchased from Cayman Chemical Co. (Ann Arbor, MI) and dimethyl sulfoxide (DMSO, 99.9% pure) from Sigma-Aldrich (St. Louis, MO).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the crystal structure of human AdipoR was determined at high resolution, which represents a novel class of receptor structure [60]. A synthetic smallmolecule (AdipoRon) and several peptides can mimic adiponectin actions through agonistic binding to the AdipoR, suggesting that small-molecule has the potential to function as an Adi-poR agonist [8][9][10]. Therefore, one possibility is that β-carotene and lycopene may function as agonists of AdipoR in activating adiponectin signaling pathway.…”
Section: Plos Onementioning
confidence: 99%
“…AdipoRon activated adiponectin signaling pathways, including AMPK phosphorylation, and contributed to the improvement of glucose metabolism disorder in vivo. In addition, several peptides have been reported to act as AdipoR agonists, activating the adiponectin signaling pathway and enhancing glucose uptake in muscle cells [9,10]. These reports indicate that low molecular weight compounds may activate the adiponectin signaling pathway and ameliorate glucose metabolism disorder.…”
Section: Introductionmentioning
confidence: 99%